The Effect of Smartboard Media on the Outcomes of Science Learning at Grade III Students of State Elementary School 124386 Pematangsiantar - Dameria Dinamita Matondang; Rio Parsaoran Napitupulu; Yanti Arasi Sidabutar (International journal of technology and education research, 2026)
This study aimed to determine the effect of Smartboard media on the science and social studies (IPAS) learning outcomes of third-grade students at UPTD SD Negeri 124286 Pematangsiantar. The study employed a quantitative approach using a quasi-experimental design with two groups, namely an experimental class and a control class. The population of this study consisted of all third-grade students at the school. The research sample included 20 students in the experimental class and 20 students in the control class. Data were collected through tests administered in the form of pretests and posttests. Prior to implementation, the research instruments were tested for validity, discrimination index, and item difficulty level. The validity test results indicated that all 20 test items were valid. The findings revealed that the average student learning outcome score in the experimental class was 87.00, while the control class obtained an average score of 76.25. Based on the hypothesis testing using the Independent Sample t-Test, the significance value (Sig. 2-tailed) was 0.002 < 0.05, indicating that Ha was accepted and H0 was rejected. Therefore, it can be concluded that the use of Smartboard media had a significant effect on the IPAS learning outcomes of third-grade students at UPTD SD Negeri 124286 Pematangsiantar.